2003
DOI: 10.1080/09593330309385555
|View full text |Cite
|
Sign up to set email alerts
|

Ozonation characteristics of bisphenol a in water

Abstract: Ozonation characteristics of bisphenol A were investigated as a function of gaseous ozone dose, initial concentration of bisphenol A, pH, radical scavenger (tert-butanol), and radical initiator (hydrogen peroxide). The ozonation led to a complete removal of bisphenol A in water within a certain period of time. The overall rate of the ozonation linearly increased with the ozone dose. The stoichiometry in the ozonation of bisphenol A was found to be 1.5 - 1.8 mole of ozone per mole of bisphenol A. The direct rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
3
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 21 publications
0
12
3
1
Order By: Relevance
“…Furthermore, at pH value of 7.0 bicarbonate ion which has a lower reactivity towards • OH compared with carbonate ion is a predominate species. In addition, the reactivity of bicarbonate and carbonate ions with aqueous ozone, 1 × 10 −2 and <1 × 10 −2 M −1 s −1 [42], respectively, is significantly lower than that of BPA reported in the literature: 1.3 × 10 4 M −1 s −1 [29] and 2.7 × 10 6 M −1 s −1 [31]. achieving about 79 and 92% at pH values of 5.0 and 7.0, respectively.…”
Section: Effect Of Bicarbonate Ioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Furthermore, at pH value of 7.0 bicarbonate ion which has a lower reactivity towards • OH compared with carbonate ion is a predominate species. In addition, the reactivity of bicarbonate and carbonate ions with aqueous ozone, 1 × 10 −2 and <1 × 10 −2 M −1 s −1 [42], respectively, is significantly lower than that of BPA reported in the literature: 1.3 × 10 4 M −1 s −1 [29] and 2.7 × 10 6 M −1 s −1 [31]. achieving about 79 and 92% at pH values of 5.0 and 7.0, respectively.…”
Section: Effect Of Bicarbonate Ioncontrasting
confidence: 61%
“…The air-to-water ratio must be very high to effectively remove BPA, which increases the cost of treatment. Non-conventional treatment techniques have been examined for the degradation of BPA, including TiO 2 photocatalyst [25], photo-Fenton process [26], sonochemical reaction [27], UV photolysis [28], and ozonation [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…This trend was not confirmed by the study of Lee et al [58], dealing with bisphenol A (BPA) ozonation at pH ranging between 2 and 12. Authors found that degradation rate was sensitive and proportional to the ozone feed rate, but insensitive to pH and BPA concentration.…”
Section: Ozonationcontrasting
confidence: 42%
“…The following discussion covers a critical review of published research on ozonebased destruction of BPA in water. Lee et al (2003) studied the degradation of BPA at pH ¼ 2, 7 and 12 and found that the rate was sensitive and proportional to the ozone feed rate, but insensitive to pH and the concentration of BPA. They found that even at extreme alkaline conditions (e.g.…”
Section: Dark Advanced Oxidation Reactions With Ozone Ultrasound Andmentioning
confidence: 99%